Manfaat PhET Simulasi Dalam Menopang Sarana dan Prasarana Laboratorium Fisika Untuk Meningkatkan Minat Belajar Siswa - Badriyah Badriyah; Restu Dwi Setiyo; Zakiya El Firdausi; Khudzaifah Nuqia; I Ketut Mahardika; Singgih Baktiarso (Jurnal Ilmiah Wahana Pendidikan, 2023)
Nowadays, technology dominates all areas of the country. The rapid advancement of technology can provide an alternative to the field of education in creating technology-based learning media. Physics Education and Technology (PhET) is an example of a technology that can support school laboratories. Physics Education and Technology (PhET) has attractive features to make objects appear more authentic. This article aimed to determine 1) the advantages of PhET in supporting school laboratories and 2) The effectiveness of using PhET simulations to enhance student learning interest. This research employed a qualitative method focusing on high school students. The data was collected using interviews; subsequently, it was analysed based on existing theory